Coral Reef‐Like Carbon Nanomaterial: Synthesis, Characterization and Mechanism Study. Issue 30 (25th October 2017) - Mahal, Ehab; Al‐Mutlaq, Shaymaà; Sonsudin, Faridah; Yahya, Rosiyah; Wei, Xiaoyi; Mahal, Ahmed
Abstract: Coral reef‐like carbon nanomaterials (referred to carbon nanotrees or nanodendrites) were successfully synthesized using waste automobile tires as an alternative source of carbon. The products have been characterized using field‐emission scanning electron microscope (FESEM), transmission electron microscopy (TEM), energy‐dispersive X‐ray spectroscopy (EDX) and Raman Spectroscopy. Thermogravimetric analysis (TGA) was investigated in order to examine the thermal stability of the products. The morphology of the products showed observation of tree‐like carbon nanomaterials similar to natural coral reef having thin graphitic outer mono shell with diameter about 3 nm and different monoliths sizes of about 7 to 40 nm. The as obtained materials demonstrated good thermal stability with a yield of 56% due to high temperature used in the deposition stage. The proposed formation mechanism suggested that they are formed as a result of the fusion and swelling of the nanoparticles. The temperature range of the deposition step in addition to the cooling step play major role in the formation of such materials. Abstract : In this study, we described the synthesis and characterization of coral reef‐like carbon nanomaterials using waste automobile tires at the nanoscale for the first time as far to our knowledge. The fusion and swelling of the nanoparticles and the temperature range of the deposition step in addition to the cooling step play major role in the formation of such materials.